1986
DOI: 10.1136/gut.27.11.1394
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis associated with small intestinal villous atrophy.

Abstract: SUMMARY Two patients diagnosed as having small intestinal hyperplastic villous atrophy and being treated with a gluten free diet were investigated because of persistent watery diarrhoea. Both were found to have collagenous colitis. Previous reports of this condition have emphasised the presence of normal small intestinal mucosal architecture and the association of collagenous colitis with intestinal villous atrophy has not previously been reported. Both cases responded to oral steroid therapy, but not to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 12 publications
1
27
1
Order By: Relevance
“…Identification of ileal inflammation may be significant in distinguishing certain inflammatory conditions such as ulcerative colitis and Crohn disease. Prior studies of lymphocytic and collagenous colitis have identified abnormal findings in the duodenum (13,14) and jejunum (15)(16)(17)(18)(19), but only a few studies have described the changes in the mucosa of the terminal ileum (1, 7, 12, 20 -24). In these studies, the terminal ileum has been shown to have normal morphological features (1,12) or to demonstrate variable degrees of villous atrophy (7,21,23,24) with or without thickening of the subepithelial collagen table (20, 22; Table: 1).…”
mentioning
confidence: 99%
“…Identification of ileal inflammation may be significant in distinguishing certain inflammatory conditions such as ulcerative colitis and Crohn disease. Prior studies of lymphocytic and collagenous colitis have identified abnormal findings in the duodenum (13,14) and jejunum (15)(16)(17)(18)(19), but only a few studies have described the changes in the mucosa of the terminal ileum (1, 7, 12, 20 -24). In these studies, the terminal ileum has been shown to have normal morphological features (1,12) or to demonstrate variable degrees of villous atrophy (7,21,23,24) with or without thickening of the subepithelial collagen table (20, 22; Table: 1).…”
mentioning
confidence: 99%
“…The histologic findings of intraepithelial lymphocytic infiltrates and epithelial injury throughout the gastric and intestinal biopsy material and the serologic presence of several autoantibodies, including antigliadin, antiendomysial, and pANCA, are unifying features. Recently, reports have shown overlap of both related and seemingly (17,(21)(22)(23)(24)(25). Associated clinical and pathologic features of these chronic inflammatory bowel diseases suggest overlapping causes or a similar pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the collagenous band-like deposition is an uneven and discontinuous process along the length of the colon, and it is found more frequently in the proximal colon than in the rectosigmoid [24,27]. There are also variations in thickness of the collagenous band-like deposit at different levels of the colon.…”
Section: Histopathological Features (Recognizable and Recognized)mentioning
confidence: 97%
“…In 1986, the first three cases of collagenous colitis, coexisting with small intestinal villous atrophy [24,25] and the first autopsy case [49] were reported.…”
Section: The Years Of Progress and Controversy (1986-1993)mentioning
confidence: 99%